True bugs (Hemiptera, Heteroptera) as psyllid predators (Hemiptera, Psylloidea) - Jerinić-Prodanović, Dušanka (Pensoft Publishers, 2013)
Abstract. Data on natural enemies of psyllids are rare and can usually be found in papers about economically significant species. During an investigation of psyllid fauna in Serbia, natural enemies were investigated, too. True bugs were the most numerous among them. From 28 psyllid species, 21 species of true bugs from families Anthocoridae and Miridae were reared. Seven species of Anthocoridae were identified: Anthocoris amplicollis (Horváth, 1839), Anthocoris confusus Reuter, 1884, Anthocoris nemoralis (Fabricius, 1794), Anthocoris nemorum (Linnaeus, 1761), Orius majusculus Reuter, 1884, Orius minutus (Linnaeus, 1758) and Orius niger Wolff, 1811. The following 14 species of Miridae were identified: Atractotomus mali Meyer-Dür, 1843, Campylomma verbasci (Meyer-Dür, 1843), Deraeocoris flavilinea (A. Costa, 1862), Deraeocoris ruber (Linnaeus, 1758), Deraeocoris lutescens (Schilling, 1836), Heterocordylus genistae (Scopoli, 1763), Hypseloecus visci (Puton, 1888), Malacocoris chlorizans Panzer, 1794, Miris striatus (Linnaeus, 1758), Orthotylus marginalis Reuter, 1884, Psallus assimilis Stichel, 1956, Psallus quercus Kirschbaum, 1856, Psallus flavellus Stichel, 1933 and Pseudoloxops coccinea (Meyer-Dür, 1843). The aim of the research was to provide list of true bugs recorded as predators of psyllids in order to preserve their diversity and significance, especially on cultivated plants.